2015
DOI: 10.1538/expanim.14-0084
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of hyperglycemia on diabetic complications in obese type 2 diabetic SDT fatty rats: effects of SGLT inhibitor phlorizin

Abstract: The spontaneously diabetic torii (SDT) fatty rat is a new model of type 2 diabetes showing overt obesity, hyperglycemia and hyperlipidemia. With early onset of diabetes mellitus, diabetic microvascular complications, including nephropathy, peripheral neuropathy and retinopathy, are observed at young ages. In the present study, blood glucose levels of female SDT fatty rats were controlled with phlorizin, a non-selective SGLT inhibitor, to examine whether and how these complications are caused by hyperglycemia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 28 publications
(48 reference statements)
1
29
0
Order By: Relevance
“…This variability in SDT fatty rats may result from differences in the development of hyperglycaemia. Indeed, although previous studies suggested that SDT fatty rats develop hyperglycaemia from a young age, the animals used in the present study showed a wide range of plasma glucose concentrations (Table ).…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…This variability in SDT fatty rats may result from differences in the development of hyperglycaemia. Indeed, although previous studies suggested that SDT fatty rats develop hyperglycaemia from a young age, the animals used in the present study showed a wide range of plasma glucose concentrations (Table ).…”
Section: Discussionmentioning
confidence: 57%
“…The Spontaneously Diabetic Torii (SDT) fatty rat is a novel animal model of type 2 DM that develops not only hyperglycaemia, but also hyperlipidaemia and insulin resistance from a young age . In the present study, we investigate whether SDT fatty rats show depression‐like behaviour using an FST.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result was in agreement with the previous report which demonstrated that the levels of serum fasting blood glucose, TG, and TC in db/db mice increased as compared to the control group, while the oral administration of phlorizin reduced these levels significantly (Cai et al, ). According to a previous report, plasma TC and glucose levels were considerably decreased in 18‐week‐old female diabetic tori fatty rats when administered subcutaneously with 100 mg/kg phlorizin (Katsuda et al, ). Another study found that high‐fat diet increased the non‐HDL‐cholesterol and plasma free fatty acid levels in rats; however, these levels were lowered significantly in the phlorizin‐treated group (0.02%, w/w) (Shin, Cho, Jung, Ryu, & Choi, ).…”
Section: Discussionmentioning
confidence: 93%
“…More than half of all individuals with diabetes exhibit one or more microvascular complications, including diabetic nephropathy (DN), diabetic peripheral neuropathy (DPN), or diabetic retinopathy (DR), which have a serious negative impact on the quality of life of patients [5,6].…”
Section: Introductionmentioning
confidence: 99%